Marshall cavendish maths. 5, (Teacher's guide) - Soon, Spario (Marshall Cavendish Education Singapore, 2017)
Marshall Cavendish Mathematics 5, Teacher's Guide is a structured resource that supports teachers in effectively delivering the Grade 5 math curriculum. It provides detailed lesson plans, clear explanations of mathematical concepts, and strategies for teaching topics such as fractions, decimals, geometry, and problem-solving. The guide offers suggestions for engaging activities, classroom discussions, and methods for assessing student understanding. It also includes tips for addressing learning challenges and differentiating instruction to cater to diverse learning needs. With its step-by-step guidance, the book helps teachers foster a positive and interactive math learning environment.